Introducing coding to young children through play-based learning activities using scratch - Lora Rahma Saputri; Jayadinata, Asep Kurnia; Ardiyanti, Dhea (Universitas Islam Negeri Raden Intan Lampung, 2026)
Background: The rapid development of digital technology has increased the need to introduce 21st-century skills, including computational thinking, from an early age. One approach that can be implemented is coding education through play-based activities that are aligned with children's developmental characteristics. Objective: This study aims to describe the implementation of coding introduction for young children through play-based activities using Scratch. Methods: This study employed a descriptive qualitative approach. Data were collected through observations, interviews, and documentation involving children aged 4–5 years in an early childhood education institution. Results: The findings revealed that coding introduction through Scratch could be implemented gradually through play-based activities. Of the eight children who participated in the study, six were able to independently arrange simple coding commands, while the remaining two required additional guidance to understand the instructions. Most children demonstrated positive responses, including enthusiasm, active participation, and high curiosity throughout the activities. Furthermore, children began to understand the cause-and-effect relationships between commands and their outcomes. The implementation was supported by engaging learning media, the availability of digital devices, and teacher assistance. However, challenges were identified, particularly differences in children's abilities and levels of understanding. Conclusion: Introducing coding through Scratch can serve as an alternative instructional approach that is appropriate for young children's characteristics because it is delivered through enjoyable play-based activities. This approach not only enhances children's engagement in learning but also supports the early development of computational thinking skills through the meaningful use of digital technology.